Antitumor Effects of Rapamycin in Pancreatic Cancer Cells by Inducing Apoptosis and Autophagy - Dai, Zhi-Jun (MDPI, 2012)
Rapamycin (Rapa), an inhibitor of mammalian target of Rapamycin (mTOR), is an immunosuppressive agent that has anti-proliferative effects on some tumors. This study aims to investigate the effects of Rapa suppressing proliferation of pancreatic carcinoma PC-2 cells in vitro and its molecular mechanism involved in antitumor activities. MTT assays showed that the inhibition of proliferation of PC-2 cells in vitro was in a time- and dose-dependent manner. By using transmission electron microscopy, apoptosis bodies and formation of abundant autophagic vacuoles were observed in PC-2 cells after Rapa treatment. Flow cytometry assays also showed Rapa had a positive effect on apoptosis. MDC staining showed that the fluorescent density was higher and the number of MDC-labeled particles in PC-2 cells was greater in the Rapa treatment group than in the control group. RT-PCR revealed that the expression levels of p53, Bax and Beclin 1 were up-regulated in a dose-dependent manner, indicating that Beclin 1 was involved in Rapa induced autophagy and Rapa induced apoptosis as well as p53 up-regulation in PC-2 cells. The results demonstrated that Rapa could effectively inhibit proliferation and induce apoptosis and autophagy in PC-2 cells.